1982
DOI: 10.1111/j.1439-0418.1982.tb03568.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prey and temperature on the development and biology of Cheyletus malaccensis Oudemans (Acari, Cheyletidae)

Abstract: Cheyletus malaccensis was fed during its life span on each of eggs, larvae, nymphs and adults of Tyrophagus putrescentiae. Both of prey eggs and larvae induced shorter periods of the predator immature stages than prey nymphs or adults. The predator food requirements seemed so be negatively correlated with the prey size, as its number successively decreased as the prey grew up. During the period of immature stages, the predator preferred prey larvae, followed by eggs, nymphs and adults. Eggs and larvae of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Several researchers have studied (aspects of) the biology of this predator, and different results were obtained, e.g., in developmental time, fecundity, reproduction mode, and prey consumption (Zaher and Soliman 1971;Summers and Witt 1973;Rizk et al 1979;Yousef 1982;Saleh et al 1986;Nangia et al 1994;Pekar and Hubert 2008). These differences may be attributed to the occurrence of various biotypes in different regions of the world (Palyvos and Emmanouel 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several researchers have studied (aspects of) the biology of this predator, and different results were obtained, e.g., in developmental time, fecundity, reproduction mode, and prey consumption (Zaher and Soliman 1971;Summers and Witt 1973;Rizk et al 1979;Yousef 1982;Saleh et al 1986;Nangia et al 1994;Pekar and Hubert 2008). These differences may be attributed to the occurrence of various biotypes in different regions of the world (Palyvos and Emmanouel 2004).…”
Section: Discussionmentioning
confidence: 98%
“…It is also the most common predatory mite in stored products in Greece (Palyvos and Emmanouel 2004;Palyvos et al 2008). It is known to prey on other mites, especially acarids, and also feeds on eggs of Ephestia cautella Walker, Corcyra cephalonica (Stainton) and Tribolium confusum Duv., and it attacks young larvae or nymphs of other insects (Rizk et al 1979;Yousef et al 1982;Nangia et al 1994). Cheyletus malaccensis is associated with both grain mass and grain residues (Hubert et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…In fact, this species was recovered from all categories of storage facilities, being dominant in silos and inXuent in stores of agricultural cooperative unions. This species feeds not only on pest mites but also on insect eggs (Rizk et al 1979;Yousef et al 1982) and it is associated with both grain mass and grain residues (Hubert et al 2006). In the present study C. eruditus, common in central and northern Europe (Hubert et al 2006;Lukas et al 2007), was found in much lower numbers.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to prey on other mites (Hughes 1976, Pekar and Hubert 2008, Cebolla et al 2009) and also feeds on eggs of Ephestia cautella Walker, Corcyra cephalonica (Stainton) (Nangia et al 1994), E. kuehniella Zeller (Athanassiou and Palyvos 2006), Tribolium confusum Duv. (Rizk et al 1979), T. castaneum (Herbst) (Cebolla et al 2009) and it attacks young larvae or nymphs of other insects (Yousef et al 1982;Sengonca et al 2004). Cheyletus malaccensis is associated with both grain mass and grain residues (Hubert et al 2006).…”
Section: Introductionmentioning
confidence: 96%